Technology and its influence on the Behavior of Class VII Students at SMP MBS Zam-Zam Cilongok - Nanang Aminanto; Ibnu Hasan; Darodjat Darodjat (Green Publisher Indonesia, 2025)
This study examines the impact of technological advancements on the behavior of seventh-grade students at SMP MBS Zam-Zam Cilongok. The research aims to determine the extent to which technological developments influence student behavior, providing insights into both the positive and negative effects of technology use in educational settings. To achieve this, the study employs a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving seventh-grade students, caregivers, and teachers. Findings reveal that technology offers positive effects, such as easier access to information and support for learning, but also poses challenges, including addiction, concentration issues, and potential exposure to negative content. The pesantren has implemented various policies to mitigate these negative effects, such as limiting gadget usage, providing digital literacy education, and strict supervision. Technology is also selectively utilized to enhance learning quality without neglecting the pesantren's traditional values. However, the implementation of these policies faces challenges, including limited resources, inconsistent adherence by students, and insufficient human resource readiness. This study underscores the importance of synergy between pesantren administrators, parents, and the community to optimize the wise use of technology in accordance with Islamic values. Furthermore, more comprehensive research is needed to gain a deeper understanding of the phenomenon. The results of this study are expected to serve as a reference for other pesantren administrators in formulating relevant policies in the digital era while supporting the pesantren's vision of shaping students who are faithful, pious, and possess noble character